A new genus and three new species of tribe Oxycerini (Diptera: Stratiomyidae) from Oriental region - Yang, Zai-Hua; Rozkošný, Rudolf; Yang, Mao-Fa (Zootaxa, 2015)
Oxyceroides gen. nov., including three new species, O. gracilis sp. nov., O. sinica sp. nov. and O. tangi sp. nov. from South China in the Oriental region are described and illustrated. Related genera from other biogeographical realms are briefly discussed. Identification keys to the known Oriental Oxycerini and to the three new species of Oxyceroides are given.